A quasi-experimental study to assess the effectiveness of abdominal deep breathing exercise on level of blood pressure and stress among hypertensive patients in selected hospitals in Jalandhar, Punjab - Raina, Neetika; Williams, Veena; George, Jophy E. (International Journal Of Community Medicine And Public Health, 2025)
Background: Hypertension, or high blood pressure, is often called a “silent disease” because it typically shows no symptoms, leaving many individuals unaware of its presence. Despite the absence of warning signs, hypertension can significantly damage the body and increase the risk of heart disease and stroke. In today’s fast-paced world, understanding how stress influences blood pressure is vital. Stress has long been identified as a key risk factor for hypertension, alongside obesity, physical inactivity, and addictions such as smoking and alcohol use. The constant hassles, deadlines, and demands of modern life contribute to mental and psychosocial stress, which can elevate blood pressure over time. Methods: This study adopted a quantitative, quasi-experimental design (one-group pre-test and post-test) to examine the effect of abdominal deep breathing exercises on stress levels and blood pressure among 60 hypertensive patients in hospitals across Jalandhar, Punjab. Participants were divided equally into an experimental group (30) and a control group (30). The modified daily stress response scale and blood pressure assessment scale were used for data collection. Results: The experimental group practicing abdominal deep breathing exercises showed a statistically significant reduction (p<0.05) in both systolic and diastolic blood pressure and stress levels compared to the control group. Conclusions: Abdominal deep breathing proved to be an effective, low-cost, and non-invasive intervention for reducing stress and managing hypertension. Incorporating such techniques into traditional treatment strategies can enhance patient outcomes.